The Cis bilamellatus species-group (Coleoptera, Ciidae) in southern Africa: Cis mooihoekite sp. n. and new distributional records - Souza-Gonçalves, Igor; Lopes-Andrade, Cristiano (African Invertebrates, 2018)
Cis mooihoekite sp. n. is described based on specimens collected at two localities in the province of Mpumalanga, South Africa. The new species is included in the Cis bilamellatus species-group, which comprises species with a single plate on both anterocephalic edge and anterior pronotal edge in males, females with pronotum usually widest near the posterior end and gradually narrowing anteriorly and both sexes with dual elytral vestiture. Cis mooihoekite sp. n. can be distinguished from the other South African species in the group by the pronotum devoid of a median impunctate line, pronotal plate angularly emarginate forming two small and triangular horns with acute apex and anterocephalic edge with very acute corners. New geographical records and information on the host fungi of Cis pickeri Lopes-Andrade, Matushkina, Buder & Klass, 2009 are provided.
Keywords: Minute tree-fungus beetles; Ciinae; Ciini; Ethiopian; Western Cape Province